121 Mediating Factors Between Caregiver Burden and Quality of Life in Caregivers of Older Patients with Newly Diagnosed Lung Cancer. (16th March 2021) - Zhu, S; Yang, C; Li, J; Mei, W
Abstract: Introduction: Family caregivers of older patients with newly diagnosed lung cancer become responsible for patients' care, usually without preparation or training in provision of care. Their efforts of care generate caregiving burden, which could deteriorate their quality of life and affect the prognosis of patients. The aims of this study were to examine associations between caregiver burden and quality of life, coping, social support for family caregivers, and to investigate whether coping and social support mediate associations between family caregiver burden and their quality of life. Methods: A cross-sectional study was performed at two thoracic surgery wards in one tertiary hospital in Changsha, China from November 2019 to May 2020. This study involved 224 family caregivers of patients aged over 50 years and newly diagnosed with lung cancer. Caregivers-reported outcomes were measured by Zarit caregiver burden interview, simplified coping style questionnaire, social support rating scale, and quality of life family version. Structural equation modeling (SEM) was used to test the hypothesized mediation model. Results: SEM indicated a good fit for the mediation model, which explained 49.7% of the variance of quality of life. Higher level of caregivers' burden was negatively associated with quality of life (r = 0.183, P = 0.042). Coping partially mediated the effect of caregiver burden on quality of life (indirect effect −0.389, P = 0.000). Social support did not mediate the relationship between caregiver burden and quality of life (indirect effect −0.023, P = 0.087). Conclusions: Caregivers' burden of patients with newly diagnosed lung cancer is correlated to quality of life which is partially mediated by coping. Early intervention providing caregivers with positive coping strategies may improve their quality of life.